CURRENT SLEEP QUALITY STATUS OF MEDICAL STUDENT PUBLIC HEALTH MAJORS AT THAI NGUYEN UNIVERSITY AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current sleep quality status of public health medical students at Thai Nguyen University of Medicine and Pharmacy and some related factors. Research method: A cross-sectional descriptive study was conducted on 311 students from first to final year of the Public Health Medical program at Thai Nguyen University of Medicine and Pharmacy in 2025.  Results: The study results showed that the rate of sleep disorders among students was 75,9% (PSQI > 5). There was a significant association between family pressure, academic workload pressure with sleep quality status (p < 0,05).  Conclusion: The study results show that the rate of sleep disorders among students is 75,9% (PSQI > 5). Therefore, greater attention should be paid to this issue to ensure the quality of learning. Students need to develop appropriate study and daily life plans. Families should provide more support for students’ mental and material well-being so that they can study with peace of mind.
Keywords: Preventive Medicine students, sleep quality, PSQI.